THE TRANSLATION OF THE DIALOGUE IN THE NOVEL “DAYS GONE BY” BY ABDULLA KADIRI (Scientific journal of the Fergana State University, 2023)
In this article the dialogue in the Russian and German  translation  of  the novel “ Days gone by” by Abdulla Kadiri is anlyzed.